JEZIK IN LOGIKA: PROBLEM DOJEMAJA IN INTERPRETACIJE V ZHANG DONGSUOVI TEORIJI (Филологические заметки, 2019)
While Zhang Dongsun can also be considered as one of the leading Chinese philosophers of the 20th Century, his criticism of sinificated Marxist ideologies marked him as a political dissident and he was consequently consigned to oblivion for several decades; only recently has his work been rediscovered by a number of younger Chinese theorists, who have shown a growing interest in his ideas. During the first three decades of the 20th Century, Zhang was one of the most influential thinkers of the Republic of China, a reputation which rested, in part, on his extraordinary ability to introduce Western thought in a way which was compatible with the spirit of Chinese tradition.His work indicates not only a profound understanding of Western theories, but also a comprehension of the linguistic structures that condition them. At the same time, Zhang also remained rooted in his own, Chinese tradition of thought. According to him, the inextricably interwoven relationship between language and logic was already evident in the system of grammatical structures; in his view, the laws of logical methods also arose from the laws of linguistic structures. Therefore, the main function of such logic is to regulate language. Due to customary modes of expression, language does not always correspond to rational principles. Thus, it became a kind of necessity, and this method developed out of this necessity. It tried to re-establish a correspondence between language and rational principles, i.e. logic. This necessity is essentially a social one and does not arise from solely rational domains, as was thought by some later scholars The present article is based upon an anlysis and interpretation of his logical and philological approaches that were rooted in an interdependence and reciprocal influence of language and thought and can also be seen in his emphasis on the close connection between language and the laws of logic.